Integrasi Teknologi Informasi dan Komunikasi dalam Pembelajaran Kelas V Sekolah Dasar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The application of learning media based on Information and Communication Technology (ICT) is an important part in improving the quality of learning in elementary schools, especially in class V of SD Al-Irsyad Al-Islamiyyah Pekalongan. This study aims to evaluate the effectiveness of using ICT media in improving interactivity, attractiveness, and flexibility of learning, as well as identifying obstacles faced during the teaching and learning process. The method used is qualitative with data collection techniques in the form of in-depth interviews with teachers, questionnaires to students, and direct observation of the learning process. Qualitative data was analyzed using a thematic approach, while quantitative data was processed descriptively and inferentially to measure student engagement and understanding. Data triangulation was conducted to ensure the validity and reliability of the findings. The results show that ICT media can increase students' motivation and involvement in learning, provide flexibility in accessing materials, but there are obstacles in the form of adjusting learning materials and limited supporting infrastructure. In conclusion, the integration of ICT media in basic learning needs to be supported by training for teachers and infrastructure development so that its implementation is more optimal and has a positive impact on the quality of education.